Analysis of the implementation of national quality indicator measurement policy on hospital accreditation achievement in Indonesia - Purwandani, Ruri; Purnamawati, Dewi; Putri, Aragar (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The measurement of Hospital National Quality Indicators (NQI) is mandatory for improving healthcare services in hospitals according to Minister of Health Regulation Number 30 of 2022. However, the achievement of NQI has not been optimal and is not in line with the hospital's accreditation status. Purpose: To determine the implementation of the NQI measurement policy on hospital accreditation status achievement using the RE-AIM framework. Method: Evaluative research was conducted at 6 selected hospitals in Indonesia representing the western, central, and eastern regions. Primary data collection was done through in-depth interviews, while secondary data were obtained from document searches. Data analysis used content analysis techniques according to the RE-AIM framework. Results: The total number of accredited hospitals up to December 2023 was 2,884 hospitals (95.6%), yet the average compliance rate for reporting National Quality Indicators in 2023 was only 69%. Utilizing the RE-AIM approach on six hospitals in Indonesia, only one hospital consistently reported NQIs, while the rest could only achieve targets of 5-8 NQIs. The NQI measurement policy proves effective in achieving accreditation goals and enhancing service quality; however, NQI measurement in these six hospitals remains suboptimal due to challenges such as leadership commitment. Nonetheless, NQI measurement shows promise with the establishment of Hospital Quality Committees/Teams and NQI reporting through the SIMAR application. The sustainability of NQI measurement in hospitals is pursued through socialization, training, and enhancing monitoring and evaluation processes. Conclusion: The implementation of NQI measurement policies in six hospitals is good but needs to be improved for routine reporting compliance and NQI target achievement. The NQI measurement policy has a positive impact on achieving accreditation goals. Suggestion: The government, through the Ministry of Health, needs to optimize advocacy for NQI measurement, implement rewards and punishments, and develop NQI reporting applications to be more effective and efficient.